New world, new perspective: a learner in community pharmacy / Nur Syazana Izati Nizan - Nizan, Nur Syazana Izati (Faculty of Pharmacy, 2024)
March 19, 2024, marked my first venture into a new page of my life story. I recalled being apprehensive about people’s expectations of me, given that I am a fourthyear student who should already know most of what I am supposed to know for community pharmacy settings. I was overthinking many possible scenarios that I may face later on while reading notes back-to-back for every mile I drove to my destination. But I am starting to look forward to it because they just warmly welcomed me every morning and eagerly taught me whatever I asked them for or what I did not know. Labelling, serving the patient, housekeeping, learning, restocking, testing blood pressure, and so much more became my routine at the pharmacy.